2014
DOI: 10.1371/journal.pone.0103214
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effects on the Flow of Powell-Eyring Fluid Past an Unsteady Inclined Stretching Sheet with Non-Uniform Heat Source/Sink

Abstract: This study investigates the unsteady flow of Powell-Eyring fluid past an inclined stretching sheet. Unsteadiness in the flow is due to the time-dependence of the stretching velocity and wall temperature. Mathematical analysis is performed in the presence of thermal radiation and non-uniform heat source/sink. The relevant boundary layer equations are reduced into self-similar forms by suitable transformations. The analytic solutions are constructed in a series form by homotopy analysis method (HAM). The converg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…It is also observed that the velocity and temperature profiles shown better enhancement in injection case compared with suction case. Tsai et al (2008), Hayat et al (2015). Under some special conditions present results have an excellent agreement with the existed results.…”
Section:   the Sheet Is In Vertical Directionsupporting
confidence: 89%
“…It is also observed that the velocity and temperature profiles shown better enhancement in injection case compared with suction case. Tsai et al (2008), Hayat et al (2015). Under some special conditions present results have an excellent agreement with the existed results.…”
Section:   the Sheet Is In Vertical Directionsupporting
confidence: 89%
“…Results are computed through homotopy analysis method. [21][22][23][24][25][26][27][28][29][30] Convergence of the constructed series solutions is ensured. Solutions expressions are analyzed via graphs and tabular values for different quantities.…”
Section: Introductionmentioning
confidence: 96%
“…On the radiation effects affecting the flow of PowellEyring fluid, Tasawar et al [6] examined the non-Newtonian fluid past an unsteady inclined stretching sheet having nonuniform heat source and sink.…”
Section: Introductionmentioning
confidence: 99%